Factors Affecting Risk Perception in Respect of Equity Shares: A Social Network Analysis Approach - Ranjit Singh; , Jayashree Bhattacharjee, and K. Kajol K. Kajol
The study intends to identify the factors that affect the risk perception of investors towards equity shares and further identifies the association between the identified factors. The study aims to conduct a thorough analysis of the factors affecting risk perception along with measurement of their influence on risk perception in respect of equity shares using Social Network Analysis (SNA). The factors influencing risk perception in equity shares have been identified through review of literature. Delphi technique was employed to determine the association between the factors and the significance of the impact of each of the factors was analysed using SNA. The study found that culture and education are most critical factors among the other factors influencing risk perception in respect of equity shares. While the factors such as capacity of investors, framing effect and loss aversion does not have much impact on the risk perception. The study will help the investors in making decision to invest in equity shares. The present study also gives avenues for the future research by providing the area where more research is needed.